On the Molise Slavic Literary Standard - Borowski, Krzysztof (Poznańskie Studia Slawistyczne, 2015)
This article aims to present and describe the situation of the literary language of the Molise Slavs. In the last decades, various scholars have expressed their views on this issue with some of them claiming that Molise Slavic is a literary language, whilst by the other ones this vernacular was denied such right. Although Alexandr D. Dulichenko – who coined the term „Slavic literarymicrolanguage” – dated its literary traditions back to the 19th century, some scholars perceive the 18th or 20th centuries as the beginning of the literature written in Molise Slavic (MSl). Consequently, this led to ambiguity that this article is trying to clarify. Until recently, this vernacular was prevalently used for poetry and short prose, but with recent publications of Nicola Gliosca’s novels, Molise Slavic is now on its way to develop as a full-fledged literary language. According to typology presented by Antoni Furdal, MSl can now – with presence of translations – be classified as a „literary language with limited sphere of use”.